2018
DOI: 10.1111/bju.14161
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and immediate management of genitourinary injuries in pelvic and acetabular trauma: a 10‐year retrospective study

Abstract: In P + A trauma cases GU injuries may be underreported because of inadequate evaluation and diagnostic investigations in these patients. We advocate robust, uniform and guideline-based evaluation of GU injuries in P + A trauma to avoid the significant long-term morbidities that are associated with misdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…and some cases were inappropriately operatively explored as a result [7]. Another study assessed patients with traumatic pelvic and acetabular fractures and found that only 47% of patients with pelvic or acetabular fractures that also had hematuria had a formal urologic evaluation on initial presentation [8]. ese findings emphasize that although guidelines are in place for appropriate bladder imaging, they are not always being followed.…”
Section: Discussionmentioning
confidence: 99%
“…and some cases were inappropriately operatively explored as a result [7]. Another study assessed patients with traumatic pelvic and acetabular fractures and found that only 47% of patients with pelvic or acetabular fractures that also had hematuria had a formal urologic evaluation on initial presentation [8]. ese findings emphasize that although guidelines are in place for appropriate bladder imaging, they are not always being followed.…”
Section: Discussionmentioning
confidence: 99%
“…Minor fractures rarely cause urethral injury, and most PFUIs result from massive blunt shearing force, and pelvic fractures with disruption of the pelvic ring . Although earlier data suggest that the incidence of PFUI is 10–25% of males with pelvic fracture, later data showed a much lower incidence (1.4–2%) . The male urethra can be subdivided into the anterior urethra and posterior urethra.…”
Section: Pathophysiology and Mechanism Of Pfuimentioning
confidence: 99%
“…2,12 Although earlier data suggest that the incidence of PFUI is 10-25% of males with pelvic fracture, later data showed a much lower incidence (1.4-2%). 4,10,13 The male urethra can be subdivided into the anterior urethra and posterior urethra. The anterior urethra consists of the fossa navicularis, penile urethra and bulbar urethra, whereas the posterior urethra consists of the membranous urethra and prostatic urethra.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with pelvic ring fractures (PRFs) these structures are injured in approximately 5% of patients [2]. lnjuries to the bladder and urethra are referred to as lower urinary tract injuries (LUTIs) and typically occur after high-energy trauma like road traffic accidents and after falls from a significant height [3,4]. Associations between PRFs and LUTIs after high energy trauma are through direct mechanisms (e.g.…”
mentioning
confidence: 99%
“…Conversely, limitations of the study are that the extent, grade, management and outcomes of each LUTI were not measured or analyzed in detail. Therefore, it is difficult to clearly determine whether more unstable PRFs resulted in higher grades of bladder and urethral injuries [4]. In addition, it is difficult to make definitive conclusions based on the relatively small numbers in the subgroup analysis.…”
mentioning
confidence: 99%